Foundations of contemporary interpretation - Silva, Moises; Silva, Moises (Grand Rapids, MI : Zondervan, 1996)
Contents : Has the church misread the Bible?/ Moises Silva; Literary approaches to Biblical interpretation/ Tremper Longman III; God, language and Scripture/ Moises Silva; The art of biblical history/ V. Philips Long; Science and hermeneutics/ Vern S. Poythress; The study of theology/ Richard A. Muller
Compilation.
Keywords: Bible -- Hermeneutics